MIRA (Introducing Community Identity): Interactive Learning Media Based on Canva for Fourth Grade Elementary School Students - Amelia, Frieska Heaven; Astuti, Tri (Universitas Pendidikan Ganesha, 2025)
The use of conventional media for abstract material makes it difficult for students to understand the learning material, resulting in low student learning outcomes. This research was conducted to analyze and describe the design development, feasibility, and effectiveness of the MIRA interactive learning media based on Canva for 4th-grade elementary school students. The type of research is Research and Development (R&D) using the Borg and Gall development model. The validation results from material experts obtained a percentage of 90% with very feasible criteria, and media experts 94% with very feasible criteria. The results of the small-scale student response questionnaire were 90% with very feasible criteria, and the large-scale student response was 96% with very feasible criteria. Meanwhile, the results of the small-scale teacher response questionnaire were 94% with very feasible criteria and the large-scale teacher response questionnaire were 96% with very feasible criteria. The results of the normality test obtained an Ltable value of 0.161 with an L0 value of 0.150 on the pretest and an L0 value of 0.089 on the post-test, so L0 < Ltable and parametric statistical techniques can be used to calculate the data because both data sets are said to be normally distributed. The test for the difference in means between the pretest and posttest yielded a tvalue of 12.365 with a ttable value of 2.064, so the tvalue is greater than the ttable value (12.365 > 2.064). Therefore, the media is effective for use in learning activities because there is a difference between the pretest and posttest scores. The average improvement test (n-gain) shows that the pretest and posttest scores experienced an average increase of 0.610 with a moderate criterion. Based on the data, the interactive learning media MIRA based on Canva can improve the learning outcomes of fourth-grade elementary school students.